10x-x=x+4+7x

Simple and best practice solution for 10x-x=x+4+7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10x-x=x+4+7x equation:


Simplifying
10x + -1x = x + 4 + 7x

Combine like terms: 10x + -1x = 9x
9x = x + 4 + 7x

Reorder the terms:
9x = 4 + x + 7x

Combine like terms: x + 7x = 8x
9x = 4 + 8x

Solving
9x = 4 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
9x + -8x = 4 + 8x + -8x

Combine like terms: 9x + -8x = 1x
1x = 4 + 8x + -8x

Combine like terms: 8x + -8x = 0
1x = 4 + 0
1x = 4

Divide each side by '1'.
x = 4

Simplifying
x = 4

See similar equations:

| 2y+(y+600)=5010 | | Y=-5/3x | | 2x-4x=4+8 | | 1/5x25 | | 8x+4y-2z= | | a^2+17+72= | | 12x+7=18x-23 | | 2x/3=x-15 | | 23=3p-1 | | x^2-6x+9*4x-x*4x-5=0 | | 20(x-5+2)=6 | | 2(y-1)-3=11 | | 2(w-1)/4=2-w | | 8(x+100)+3=837 | | 4xw*5w= | | 8x^2-56x+96=8(x-3)(x-4) | | -6x=42y | | 3g+5(g-2)= | | 64=n-8 | | 15p+16q+p-5q-4p= | | y-5x=-30 | | 6x^2-6xy= | | 3(2x-1)+2x=1-4(x-2) | | 6(1)-2y=6 | | 14a+15b+5c+4c-4b-2a= | | 3d+9e+10d+8e= | | 2x/3=x-5 | | 4/3×-1/2= | | 4/3×-1/2=0 | | 5x+18=3(6-x) | | x=5/(400-20x) | | 14.6+14.6= |

Equations solver categories